PERBANDINGAN BODY CONDITION SCORE, SERVICES PER CONCEPTION, CALVING INTERVAL, DAN DAYS OPEN SAPI FRIESIAN HOLSTEIN (FH) DI KEMITRAAN GREENFIELD DENGAN KUD TANI WILIS SENDANG - Cahya P., Aghid; Mulyati, Sri; Suwarno, Suwarno; Mustofa, Imam; Srianto, Pudji; Utomo, Budi (Ovozoa: Journal of Animal Reproduction, 2019)
The purpose of this study was to determine the comparison of Body Condition Score, Services Per Conception, Calving Interval, and Days Open cow friesian holstein (FH) in Greenfield Partnership and Tani Wilis Sendang Cooperation. The material used in this research is dairy cattle that have been inseminated in Greenfield Partnership and KUD Tani Wilis with secondary data retrieval of reproduction notes during IB until partus and quisioner distributed by farmers and inseminators. The exploratory survey method used is secondary data obtained from the record reproduction inseminator. The observed variables BCS, S/C, CI and DO . The data was processed using descriptive analysis to get a number BCS, S/C, CI and DO in Greenfield Partnership and Tani Wilis Sendang Cooperation. The results showed that the average value of BCS at Greenfield Partnership is 4.86 and at Tani Wilis Cooperation is 4.74. The average value of S/C in Greenfield Partnership is 4.36 and at Tani Wilis Sendang Cooperation is 2.06. The average value CI at Greenfield Partnership is 463.00 and at Tani Wilis Sendang is 414.40. The average value DO at Greenfield Partnership is 64.84 and at Tani Wilis Sendang is 88.00. It can be concluded that the comparison of BCS in both places is not significantly different while for the S/C of Tani WilisSendang Cooperation is better than Greenfield Partnership, the CalvingInterval in both places is still less good because it is far from the standard CI value, and for the Days Open Greenfield partnership is better thanTaniWilisSendang Cooperation.